Functional and anatomical 3D-printed models for cardiovascular research and education (Transactions on Additive Manufacturing Meets Medicine, 2020)
Modern cardiovascular interventions focus on the reduction of trauma via minimally invasive access and on individualized treatment addressing anatomical and patho-physiologic differences among patients. This focus poses numerous new challenges as interventions often require image guidance, without direct sight, and enhanced preoperative understanding for better planning and navigation. Additionally, medical education needs to be adapted to the better prepare surgeons and interventional cardiologists to these challenges. Both computational and physical models ("patient twins") provide therefore ideal tools for enhanced therapy and education truly at the point-of-care. In this talk examples of anatomical and functional 3D-printed and computational models will be presented that highlight how 3d modeling helps improving cardiovascular therapies.
Keywords: cardiovascular